Determination of Thrombin Activity by Reversed-phase High Performance Liquid Chromatography - Zhang, Liang; Yang, Dehui; Liu, Ye (Current Pharmaceutical Analysis, 2023)
Background: A reversed-phase high-performance liquid chromatographic method for determining thrombin activity is described. The improved method can provide a high resolution between substrate Nα-P-toluenesulfonyl-L-arginine methyl ester (TAME) and the product of enzyme reaction, Nα-P-toluenesulfonyl-L-Arginine (TA). Methods: When the substrate concentration was 5 mg/mL, the Michaelis equation approached the zero-order reaction, and the thrombin enzyme activity must have a good linear relationship with the consumption of TAME or the yield of TA. Results: The method is suitable for quantitatively analyzing thrombin activity in formulation or serum. Conclusion: Three batches of thrombin lyophilized preparations were determined for activity.
Keywords: HPLC analysis